PENDAMPINGAN MASYARAKAT DALAM UPAYA MENJAGA KESEHATAN LINGKUNGAN DI DESA BRABE KECAMATAN MARON KABUPATEN PROBOLINGGO - Putri Nurul Fatika; Pudji Rahmawati (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
. Brabe Village, which is located in Maroon District, Probolinggo Regency, faces environmental problems that affect public health, including high stunting rates. The aim of this research is to identify the main problems related to environmental management, especially waste and sanitation, and propose solutions through educational programs and "healthy home" competitions. Improper waste management and the behavior of people who continue to throw away waste carelessly are the main causes of environmental pollution which worsens health conditions. This researcher involves the community in competition activities to increase awareness about the importance of environmental cleanliness and waste management. This program has succeeded in increasing public awareness of the importance of environmental cleanliness and that waste processing can reduce stunting rates and infectious diseases such as dengue fever. The results demonstrate the importance of increasing community awareness and involvement to create healthier environments and support children's future health.